Predictors of Social Entrepreneurial Intention in Undergraduate Students in Padang City - Jadmiko, Purbo; Azliyanti, Eflitra; Yuliviona, Reni (KnE Social Sciences, 2022)
The purpose of this study was to analyze the antecedents of social entrepreneurial intention among students. This research involved 250 respondents from various public and private universities in the city of Padang. Multiple regression analysis techniques were used to analyze the data. The results showed that self- efficacy, prosocial motivation, and intrinsic motivation had significant positive effects on social entrepreneurial intention. Student confidence in succeeding in establishing a social enterprise was very influential for social entrepreneurial intention. The novelty of this research is that it involved an element of Minangkabau culture in the consideration of social entrepreneurial intention, in terms of Minangkabau women in the city of Padang. The findings indicated that Minangkabau female students were interested in and concerned with social problems. Other theories that are relevant to the topic of social entrepreneurial intention also need to be examined to broaden the understanding of social entrepreneurship. This research focused on the social entrepreneurial intention of students, but further research should include respondents who are female Minangkabau entrepreneurs. In addition, it is necessary to analyze gender differences in the context of cultural differences, especially in developed and developing countries. Keywords: social entrepreneur, social entrepreneurial intention, self-efficacy, pro- social motivation, intrinsic motivation